Kedudukan Ulama dalam Pemerintahan Menurut Ayatullah Shariatmadari - M, Afrizal (Jurnal Usuluddin, 2004)
This article elaborates the position and roles of Islamic scholars (ulama) in goverment from Ayatollah Shariatmadari point of view. He expounds that ulama should not involve in goverment unless in certain condition like in the case of emergency. The role of ulama is monitoring and ensuring that Islamic law or syariah have been practiced in Muslim society. If Islamic leader in Islamic country does not practice or neglect syariah, ulama should play their role to advise and may be oppose them. This article will also elaborates Ayatollah Shariatmadari opinion which in certain aspect contrary to Khomeini in this issue.